Cinematic responsibility after 9/11. - Goh, Wee Kiat. (2010)
Between 2008 and 2011, in post-2000 cinematic history, a large number of films about the Holocaust, the historic systematic massacre of Jews by German Nazis, were released. These films both feature and documentaries, avoid an “active-German-Nazi-against-passive-Jewish-victim” narrative as well as depending exclusively on historical footage. The three documentary films, As Seen Through These Eyes, Four Seasons Lodge and Defamation (2009) discuss about the Holocaust without sole dependence on historical footage of German concentration camps. Films like Inglourious Basterds and District 9 (2009) disrupt the historical narrative of German Nazis as villains and Jews as victims. This research paper investigates two major questions: Firstly, when viewing a film about the Holocaust, how can the viewer bear responsibility to the Other? Secondly, why is there a return of Holocaust films in recent years? Films like Mark Herman’s The Boy in Striped Pyjamas (2008) and Stephen Daldry’s The Reader (2008), with their unresolved conclusions, fail to allow viewers to gain a catharsis. According to Emmanuel Levinas’ concept of displacement of time, the film ends, becomes a thing of the past, the failure of catharsis causes the viewer to return to it, to keep bearing responsibility to the film, while moving to the future. Secondly, through Levinas’ discontinuous, infinite and fecund time, I argue that a displacement of history occurs. Now, the “fate” of 9/11 enters into the “fate” of the Holocaust. Through this displacement of history, recent Holocaust films can arguably be ethical responses to post-9/11 politics.